Evaluation of the Impact of Offshore Wind Power and Photovoltaics on Seascape Visual Quality - LU Jiayi; TAN Xiaoxuan; JIANG Xinwei; GUO Jin (Haiyang Kaifa yu guanli)
The implementation of offshore wind power and photovoltaic projects is one of the important ways to realize the dual-carbon goal, but its visual impact on the surrounding environment is an important factor hindering its implementation. This paper tries to apply seascape sensitivity (Sa) on offshore projects to quantify the visual impact generated by offshore wind power and photovoltaic projects. The results show that (1) taking offshore wind power project's turbine hub height away from the sea level distance of 200 m, and 30 km away from the field area, the Sa in the lower value of 0.000 67, is located in the vista zone seascape. In the human field of view basically only presents the outline of the turbine; (2) take the offshore photovoltaic project photovoltaic array panels from the sea level height of 10 m, and in the 200 m away from the shore, the Sa=0.05, in the lower value, has been located in the vista belt seascape. In the human vision of the field of view basically only presents the outline of the photovoltaic array; (3) When offshore distance was taken as 500 m, the relative visual height of view was taken as 0 m, 50 m and 100 m on the offshore wind power project and offshore photovoltaic project, the value of offshore wind power project's Sa decrease with the relative visual height increase, and the value of offshore photovoltaic project's Sa increase with the relative visual height increase, but are both in the lower seascape sensitive values. Under the current requirement of offshore distance for offshore wind power and offshore photovoltaic projects, elements such as turbine hub and photovoltaic array panels are weakened, which greatly reduces the visual impact on people.